Optimal Length of Follow-up for the Detection of Unsuccessful Pediatric Pyeloplasty: A Single-Center Experience - Bansal, Utsav K.; Dangle, Pankaj P.; Stephany, Heidi; Durrani, Asad; Cannon, Glenn; Schneck, Francis X.; Ost, Michael C. (Frontiers in Pediatrics, 2017)
Objectives To assess the optimal length of follow-up for patients undergoing both open and minimally invasive pyeloplasties to ensure prompt detection of a recurrent obstruction. There are no standard guidelines on ideal follow-up and imaging post-pediatric pyeloplasty currently. Methods A retrospective chart review identified 264 patients (<18 years old) who underwent pyeloplasty for ureteropelvic junction obstruction between April 2002 and December 2014. Ultrasound was obtained every 3-4 months for the first year following pyeloplasty and thereafter at discretion of treating physician. Patient characteristics including symptoms and imaging were reviewed. Results Of the 264 patients, 72% were male with mean age of 51 months and follow-up of 26.8 months. Approximately 73% followed-up to three years. Fourteen patients (5.3%) had a recurrent obstruction. Among the failures, 85% were diagnosed and underwent successful redo-pyeloplasty within three years. The six infants with recurrence (43% of all unsuccessful surgeries) were diagnosed within three years of the initial surgery. Patients undergoing a minimally invasive procedure were less likely to be followed for more than three years compared to an open procedure (p<0.001). Patients with severe hydronephrosis preoperatively were followed longer (p=0.031). Age at surgery and type of surgical approach (p<0.01) were significant predictors of length of follow-up in a negative binomial regression. Conclusions Based on the results, a minimum of three years of follow-up is necessary to detect the majority of recurrent obstructions. Amongst those who require a secondary pyeloplasty, younger patients with severe hydronephrosis are at an increased risk of recurrence.